Negócios processuais e administração pública dialógica: a (in)suficiência do art. 190 do CPC/2015 às convenções pela Fazenda Pública. - Lelis, Bruno Kiefer (2020)
Does the general clause of procedural negotiation constitute sufficient legal permissiveness to regulate the negotiability of the Public Administration procedural prerogatives in court, especially in the case of its current consensual administrative profile? In order to answer this question, the evolution of the Public Administration profile is discussed, through a critical analysis of the called “column of the administrative legal regime” - supremacy and unavailability of the public interest - as well as the new model is evaluated procedural arising from the promulgation of the 2015 Code of Civil Procedure and its repercussions on the performance of the Public Administration in court. In the same measure, the typology of procedural juridical businesses is distinguished in the panorama of the theory of legal fact, advancing to a general analysis of the institute with CPC/2015 and closing with its specific approach when used by the Public Administration for the purpose of negotiating its prerogatives procedural. As for the methodology, an analytical and normative dogmatic approach we made, through a literature review and the norms that make up both the area of Civil Procedural Law, as well as General Law Theory and, obviously, Administrative Law. At the end, it is concluded that the general clause of procedural negotiation is sufficient to regulate the negotiability of the procedural prerogatives of the Public Administration in court, where the eventual regulation by the entities would serve only as a recommended measure, but not essential for the instrument to be signed.